Skin disorders in diabetes mellitus: an epidemiology and physiopathology review. Issue 1 (December 2016) - Macedo, Geisa; Nunes, Samanta; Barreto, Tania
Abstract Skin disorders, usually neglected and frequently underdiagnosed among diabetic patients, are common complications and encounter a broad spectrum of disorders in both type 1 and type 2 diabetes mellitus (DM)—e.g. cutaneous infection, dry skin, pruritus. Skin disorders are highly associated with increased risk of important outcomes, such as skin lesions, ulcerations and diabetic foot, which can lead to major complications and revolve around multifactorial factors besides hyperglycemia and advanced glycation end products. Although diabetic's skin disorders are consistent in the literature, there is limited data regarding early-stage skin disorders in DM patients. Disease control, early-stage treatment (e.g. skin hydration, orthotic devices) and awareness can reduce morbidity of DM patients. Thus, better understanding of the burden of skin disorders in DM patients may raise awareness on prevention and management. Therefore, the aim of this study is to perform a literature review to evaluate the main clinical characteristics and complications of skin disorders in diabetic's patients. Additionally, physiopathology early-stage skin disorders and dermocosmetic management were also reviewed.